Hydrogeochemical and isotopic characterisation of groundwater in a sand-dune phreatic aquifer on the northeastern coast of the province of Buenos Aires, Argentina - Carretero, Silvina Claudia (2013)
This contribution presents the hydrochemical and isotopic characterisation of the phreatic aquifer located in the Partido de la Costa, province of Buenos Aires, Argentina. In the sand-dune barrier geomorphological environment, groundwater is mainly a low-salinity Ca-HCO 3 and Na-HCO 3 -type, being in general suitable for drinking, whereas in the continental plain (silty clay sediments), groundwater is a Na-Cl type with high salinity and unsuitable for human consumption. The general isotopic composition of the area ranges from-6.8 to-4.3 ‰ for δ 18 O and from-39 to-21 ‰ for δ 2 H, showing that rainwater rapidly infiltrates into the sandy substrate and reaches the water table almost without significant modification in its isotopic composition. These analyses, combined with other chemical parameters, made it possible to corroborate that in the eastern area of the phreatic aquifer, there is no contamination from marine salt water.